2021
DOI: 10.1302/0301-620x.103b6.bjj-2020-2287.r1
|View full text |Cite
|
Sign up to set email alerts
|

High-volume revision surgeons have better outcomes following revision total knee arthroplasty

Abstract: Aims It has previously been shown that higher-volume hospitals have better outcomes following revision total knee arthroplasty (rTKA). We were unable to identify any studies which investigated the effect of surgeon volume on the outcome of rTKA. We sought to investigate whether patients of high-volume (HV) rTKA surgeons have better outcomes following this procedure compared with those of low-volume (LV) surgeons. Methods This retrospective study involved patients who underwent aseptic unilateral rTKA between J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…There is no consensus within the orthopaedic community to guide an acceptable outcome or benchmark following RTKA, however our results would support the opinion of centralized RTKA teams to improve patient outcomes. 23 Certainly, the pursuit of improved function, fewer complications, and greater patient reported satisfaction are goals of the orthopaedic community and the focus of future endeavours.…”
Section: Discussionmentioning
confidence: 99%
“…There is no consensus within the orthopaedic community to guide an acceptable outcome or benchmark following RTKA, however our results would support the opinion of centralized RTKA teams to improve patient outcomes. 23 Certainly, the pursuit of improved function, fewer complications, and greater patient reported satisfaction are goals of the orthopaedic community and the focus of future endeavours.…”
Section: Discussionmentioning
confidence: 99%
“…High-volume hospitals and surgeons are associated with improved outcomes, including reduced complication and readmission rates, following hip/knee revisions. 18,21 Perhaps more notable, however, is the data describing disparities in travel burden and access in a hypothetical scenario wherein patients change New York state hospitals for their revision hip/knee surgery. The study of 37,147 revision total joint arthroplasty patients identified increased travel distance for Hispanic patients who transferred care to the nearest higher volume institution from the lowest 50% by volume hospitals (OR 12.3) relative to nonHispanic counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…The study sample included adult patients (≥18 y) who underwent elective gastrectomy, pneumonectomy/lobectomy, proctectomy, or revision hip/knee arthroplasty between January 1, 2010, and December 31, 2017. These procedures were chosen because they are high cost, associated with considerable morbidity, and frequently the focus of centralization policies 18–29. Three eligible complex procedures (esophagectomy, cystectomy, and pancreatectomy) were excluded as they were noted to be highly centralized in Maryland before GBR enactment (Supplemental Figure S1, Supplemental Digital Content 1, http://links.lww.com/SLA/E319 and Supplemental Table S1, Supplemental Digital Content 1, http://links.lww.com/SLA/E319).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This trend is creating an exceedingly large demand for these procedures. We have shown that higher volume revision surgeons have better outcomes when performing rTKA than lower volume surgeons, highlighting the necessity of keeping these surgeons interested and incentivized to provide this type of service to their patients [ 12 ]. Failure to appropriately incentivize surgeons to perform these procedures may lead to a dearth of orthopaedic surgeons willing and able to take on these complicated revisions.…”
mentioning
confidence: 99%